Molecular features of renal cell carcinoma: early diagnostics and perspectives for therapy - O. V. Kovaleva; O. R. Nazarova; V. B. Matveev; A. N. Gratchev (Успехи молекулярной онкологии, 2015)
Kidney cancer (renal cell carcinoma) is one of the major problems of modern urological oncology. In Russia renal cell carcinoma accountsfor 4.3 % of all cancers. The global incidence of renal cell carcinoma has increased over the past two decades. Worldwide renal cell carcinoma accounts for 3.6 % of all cancers and is 10th frequent malignancy. For some malignancies, for instance tumours of prostate, there are markers known that allowed improved early diagnostics. Kidney cancer, however, remains to be hard to diagnose and to treat, since the symptoms can be detected on advanced stages of the disease. In Russia 75.4 % of renal cell carcinoma cases detected at the stage of local and locally advanced disease. Though there are various target drugs on the market aimed to treat this disease, the results of renal cell carcinoma treatment did not reach any substantial success. Most of existing target drugs for kidney cancer treatment include inhibitors of a single signalingpathway regulated by VHL1, which expression is lost in the vast majority of renal-cell carcinomas. Till now existing drugs did not reach sufficient efficacy. Therefore, it is highly important to search for new signaling pathways, regulating such cellular processes as proliferation, migration and apoptosis. Further, prognostic markers and therapy targets identified so far are not sufficient and poorly specific. Therefore identification and validation of new markers, and especially new specific targets for the treatment of kindey oncopathologies is highly important and timely task.